Threshold : emergency responders on the US-Mexico border - Jusionyte, Ieva, 1983- (California series in public anthropology ;, 2018)
"Emergency responders on the US-Mexico border operate at the edges of two states. They rush patients to trauma centers across state lines, tend to the broken bones of migrants who jump over the fence, and put out fires that know no national boundaries. Paramedics and firemen on both sides of the border are tasked with saving lives and preventing catastrophe in the harsh terrain at the center of divisive national debates. Ieva Jusionyte's years of experience as a paramedic provide the background for her gripping examination of the politics of injury and rescue in the militarized region surrounding the US-Mexico border. Operating in this area, firefighters and paramedics are torn between their mandate as frontline actors and their responsibility as medical professionals, and between the limits of law and pull of ethics. They occupy a position from which we can understand the practical dilemmas and the conceptual paradoxes of sovereignty and governance. Through beautiful ethnography and a uniquely personal perspective, Threshold provides a new way to understand politicized issues ranging from border security and undocumented migration to public access to healthcare today."--Provided by publisher.